Investigation of electrolyte leaching in the performance degradation of phosphoric acid-doped polybenzimidazole membrane-based high temperature fuel cells - Jeong, Yeon Hun; Oh, Kyeongmin; Ahn, Sungha; Kim, Na Young; Byeon, Ayeong; Park, Hee-Young; Lee, So Young; Park, Hyun S.; Yoo, Sung Jong; Jang, Jong Hyun; Kim, Hyoung-Juhn; Ju, Hyunchul; et al. (ELSEVIER SCIENCE BV, 2017)
Precise monitoring of electrolyte leaching in high-temperature polymer electrolyte membrane fuel cell (HT-PEMFC) devices during lifetime tests is helpful in making a diagnosis of their quality.changes and analyzing their electrochemical performance degradation. Here, we investigate electrolyte leaching in the performance degradation of phosphoric acid (PA)-doped polybenzimidazole (PBI) membrane-based HT-PEMFCs. We first perform quantitative analyses to measure PA leakage during cell operation by spectrophotometric means, and a higher PA leakage rate is detected when the current density is elevated in the cell. Second, long-term degradation tests under various current densities of the cells and electrochemical impedance spectroscopy (EIS) analysis are performed to examine the influence of PA loss on the membrane and electrodes during cell performance degradation. The combined results indicate that PA leakage affect cell performance durability, mostly due to an increase in charge transfer resistance and a decrease in the electrochemical surface area (ECSA) of the electrodes. Additionally, a three-dimensional (3-D) HT-PEMFC model is applied to a real-scale experimental cell, and is successfully validated against the polarization curves measured during various long-term experiments. The simulation results highlight that the PA loss from the cathode catalyst layer (CL) is a significant contributor to overall performance degradation. (C) 2017 Elsevier B.V. All rights reserved.